The Influence of Initial Conditions on the Swelling Potential and Swelling Pressure of Cikarang’s Expansive Soil - Simanjuntak, Murydrischy Panatap; Rahayu, Wiwik (ASTONJADRO, 2025)
Expansive soil can cause damage to simple constructions such as roads and houses with loads less than 20 kPa. Damage occurs due to the swelling behavior of expansive soil, due to changes in the moisture content of the soil. This research aims to determine the impact of the percentage of swelling potential and swelling pressure on expansive soil in the Delta silicon, West Java. This expansive soil is known to have very high swelling potential criteria. The samples used had variations in moisture content of 27% and 32%, with variations in initial stress of 16 kPa, 36 kPa, 38 kPa, and 42 kPa. The deformation that occurs due to swelling shows that all samples will continue to increase swelling for 4320 minutes (3 days). The results on the value of swelling potential and swelling pressure are influenced by water content. When a sample with a water content of 27% was compressed with a initial stress of 36 kPa, the swelling potential value increased by a maximum of 11%, and the maximum swelling pressure value was 913 kPa. These test results confirm the presence of very high soil swelling in the test area located in the silicon delta. The results of identification and swelling tests in the laboratory show that the development potential value of this land is high, which causes a high level of damage to simple construction.